An Approximative Method for Analyzing the Magnetic Field Data to Determine the Location of Preferential Flow Paths in Earthen Dam - Huynh, Thi Thu Huong; Le, Thanh Tai; Lai, Viet Hai; Bui, Trong Duy; Nguyen, Huu Quang; Dang, Quoc Trieu; Vuong, Duc Phung; Le, Van Son (Old Journal, 2020)
The AC magnetic field method allows locating the preferential flow path in the body and foundation of the earthen dam based on the magnetic signals produced by the alternating current flowing in a permeable zone. This paper presents an approximate method for analyzing the magnetic field to determine the location of the flow path in 3D. This method was verified on a hypothetical model built on ANSYS software and 3D physical model and then tested on magnetic field data measured at the study dam. The results show the feasibility of the proposed calculation method with the spatial error between the calculated flow path and the flow paths of the models below 12%. The result of the simulated magnetic field generated by the calculated flow path based on data measured at the dam shows the normalized root-mean-square error between the two sets of measured data and simulated data is about 30%.